“Górka Lubartowska-Niedźwiada” deposit (E Poland) as a potential source of glauconite raw material - Natkaniec-Nowak, Lucyna; Piestrzyński, Adam; Wagner, Marian; Heflik, Wiesław; Naglik, Beata; Paluch, Jan; Pałasz, Krzysztof; Milovská, Stanislava; Stach, Paweł (Gospodarka surowcami mineralnymi, 2019)
The main subject of research in this paper is glauconite with its useful parameters, which is the object of exploitation in the “Górka Lubartowska-Niedźwiada” deposit. The main glauconitic horizon (lower Eocene) is built by loamy fine-grained and medium greenish sands with marine fauna and fragments of amber (ca. 7 m thick). Thin lamins and pockets of silts containing phosphorites and also glauconitic sands with underlaying very thin quartz-glauconitic sands are found at the bottom of this layer. The glauconite deposit in “Górka Lubartowska-Niedźwiada” is an amount of ca. 30% by volume of the main glauconitic horizon. Glauconite of the 1M polytype (XRD) shows large granulometric and morphological differentiation (SEM-EDS). It frequently contains aggregations of euhedral or framboidal pyrite grains (RS), which is indicative of the euxinic nature of the formation environment of the rocks under study. The individual glauconite grains show distinct chemical variability, manifested in a lower share of Al2O3 and an increased content of MgO and CaO (EPMA, XRF). At the same time, a large share of K2O (above 8% by weight) allows it to be included in highly matured glauconite, thus it can be considered as a potential raw material for the production of mineral fertilizers. The association of glauconite with phosphates (SEM-EDS) and anatase inclusions in the grains of glauconite (RS) indirectly point to the contribution of the decomposing organic matter to the formation of grains of this mineral. The xylite fragments preserved in the sediment show a low degree of coalification, which is typical of soft lignite. This also shows that the transformation process was taking place under a relatively small overburden.